Al-Qur'an Solution to Yusuf's Letter in Overcoming Youth Moral Degradation in the Era of 4.0 (Study of Analysis of Moral Values Using the Story Method in Prophet Yusuf AS's Example Material) - Ruri Afria Nursa; Mhd Lailan Arqam (At-Ta'dib, 2020)
In the era of 4.0, life in Indonesia has progressed, this certainly means that human resources must continue to make improvements, both in terms of science, technology, and morals. One of these improvements can be carried out by adopting an education system as the moral message contained in the story of the prophet Yusuf. which is contained in the word of Allah swt Al-Qur'an surah Yusuf. In the story of the prophet Yusuf, there are many educational values that can be used as a source of learning, especially regarding the faith of faith and the greatness of the morals or morals of Islamic youth. However, along with the times in the era of 4.0, the all-digital era has caused the moral degradation of adolescents. Therefore, researchers are interested in knowing the solution of the al-quran surah Yusuf in overcoming the moral degradation of adolescents through the example story of the prophet Yusuf as. In its implementation, the type of research used is the type of library research which emphasizes library analysis. The data taken is literature data that uses library sources in obtaining research data. Research conducted, researchers see the objectives and data of this study using a qualitative approach